Intrinsic Kinetics of the Chlorination of RuO2 with Cl2 Between 973 K and 1073 K (700 °C and 800 °C) - Guibaldo, Cristina Noemi (2016)
Ruthenium, as well as the rest of the platinum-group metals, is of crucial importance for industry due to its extraordinary catalytic activity and high-tech applications. Because of its scarcity and high value, there is an increasing interest towards its recovery from wastes. Chlorination metallurgy arises as one possible recovery method. The intrinsic kinetics of the chlorination of ruthenium oxide was studied with the aim of applying this process in a suitable recovery technology. Chlorination of RuO2 was investigated for temperatures between 973 K and 1073 K (700 °C and 800 °C) and chlorine partial pressure from 50 to 90 kPa. The reaction rate was measured by gravimetry and the rate equation was obtained. An activation energy of 259 ± 6 kJ mol−1 and a reaction order of 0.5 with respect of chlorine partial pressure were determined. The reaction product is unstable at atmospheric conditions. Formation of RuO2Cl2 is proposed based on experimental evidence; however, such product has not been confirmed yet.